What happened - Clinton, Rodham Hillary (London Simon and Schuster, 2017)
For the first time, Hillary Rodham Clinton reveals what she was thinking and feeling during one of the most controversial and unpredictable presidential elections in history. Now free from the constraints of running, Hillary takes you inside the intense personal experience of becoming the first woman nominated for president by a major party in an election marked by rage, sexism, exhilarating highs and infuriating lows, stranger-than-fiction twists, Russian interference, and an opponent who broke all the rules. This is her most personal memoir yet.
Includes index
Keywords: Hillary Rodham Clinton